Hubungan Imunoekspresi Human Telomerase Reserve Transcriptase (hTERT) dan Vascular Endothelial Growth Factor (VEGF) dengan Gradasi Histopatologi Meningioma - Betty Marlina; Anglita Yantisetiasti; Abdul Hadi Hassan; Bethy S Hernowo (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background: Meningioma is a tumor composed of cells of neoplastic meningothelial (arachnoidal) cells that a rise from the arachnoid membrane and the layer of the arachnoid villi associated with intradural venous sinuses and surrounding tissue. Meningiomas tumors is one of the central nervous system (CNS) the most commonly found (the second sequence) and generally grow slowly. Approximately 60-95% activity of telomerase (hTERT ) found on meningiomas and can induces VEGF . The aim of this study is to determine the role of hTERT and VEGF in meningiomas grading . Methods : This study is conducted using analytic observasional cross sectional method and had been analyzed with  unpaired categorical analysis of the 60 cases of meningioma (46 cases grade I, 7 cases grade II, and7 cases grade III). The sample were obtained the archive of Anatomical Pathology Department, Faculty of Medicine, Padjadjaran University/Dr. Hasan Sadikin Hospital Result : The result of this study showed: 44 cases (96%) grade I meningiomas showed positive hTERT imunoexpression weak to strong, 2 cases(4%) non-reactive and VEGF imunoexpression showed strong positive 12 cases (26%), 24 cases(52%) were moderate positive and 10 cases (22%) weak positive. 7 cases (100%) grade II showed a strong positive hTERT imunoexpression and 5 cases (71%) showed a strong positive VEGF imunoexpression, 2 cases (29%) were moderate positive. 6 cases (86%) grade III showed strong positive hTERT imunoexpression, 1 case (14%) were moderate positive and 7 cases(100%) showed a strong positive VEGF imunoexpression. Statistical analysis revealed imunoexpression VEGF showed stronger positivity with p- value = 0.02 (< 0.05) compared to the hTERT imunoexpression with p-value =  0.73 (> 0.05). Conclusion : More affecting angiogenesis gradations meningiomas, seen by the presence of VEGF higher imunoexpression on higher gradations. hTERT Imunoexpression cannot determine of the meningiomas histopathological grading.